METHOD OF CALIBRATING AND OPERATING A DIRECT NEURAL INTERFACE SYSTEM - YELISYEYEV, Andriy; STROKOVA AKSENOVA, Tetiana (2018)
A method of calibrating a direct neural interface system comprising the steps of: a. acquiring electrophysiological signals representative of a neuronal activity of a subject's brain over a plurality of observation time windows and representing them in the form of a N+1-way tensor (X), N being greater or equal to one, called an observation tensor; b. acquiring data indicative of a voluntary action performed by said subject during each of said observation time windows, and organizing them in a vector or tensor (y), called an output vector or tensor; and c. determining a (multi-way) regression function of said output vector or tensor on said observation tensor.